ANALFANAUTAS Y LA CUARTA PANTALLA: AUSENCIA DE INFODIETAS Y DE COMPETENCIAS MEDIÁTICAS E INFORMACIONALES EN JÓVENES UNIVERSITARIOS LATINOAMERICANOS - Dr. Luis M. ROMERO-RODRÍGUEZ ,Ddo. Ángel TORRES-TOUKOUMIDIS,Dra. M. Amor PÉREZ-RODRÍGUEZ,Dr. Ignacio AGUADED (Fonseca, Journal of Communication, 2023)
Mobile devices have become an integral part of our lives. Through these terminals, users can not only communicate with their peers, but receive and produce vast amounts of information usually through social networks, making us in many ways in mass media. However, the question arises are we ready for it? In this research the problem of analfanauts understood as those individuals who dominate the digital skills necessary to interact with ICT is addressed, but lack sufficient media and information skills to avoid misinformation and structural infoxication present in the networks.